2014
DOI: 10.1002/jbm.a.35179
|View full text |Cite
|
Sign up to set email alerts
|

Rates ofin vivo(arterial) andin vitrobiocorrosion for pure magnesium

Abstract: The development of magnesium-based materials for bioabsorbable stents relies heavily on corrosion testing by immersion in pseudophysiological solutions, where magnesium degrades faster than it does in vivo. The quantitative difference in corrosion kinetics in vitro and in vivo is largely unknown, but, if determined, would help reduce dependence on animal models. In order to create a quantitative in vitro-in vivo correlation based on an accepted measure of corrosion (penetration rate), commercially pure magnesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 40 publications
0
59
0
Order By: Relevance
“…In an effort to reduce the considerable obstacles present in the developmental path of new metallic materials, we have recently developed a simplified approach for evaluating candidate stent materials in vivo [24, 25, 2931]. In this model, a wire of the selected material (simulating an individual stent strut) is implanted into the rat abdominal aorta.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to reduce the considerable obstacles present in the developmental path of new metallic materials, we have recently developed a simplified approach for evaluating candidate stent materials in vivo [24, 25, 2931]. In this model, a wire of the selected material (simulating an individual stent strut) is implanted into the rat abdominal aorta.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, a wire of the selected material (simulating an individual stent strut) is implanted into the rat abdominal aorta. With this approach, we have shown that magnesium corrodes too rapidly to be used as the base material for a stent without first undergoing considerable metallurgical modification to safely reduce the corrosion rate [24]. Similarly, we have demonstrated that iron undergoes a harmful mode of corrosion, as it produces a voluminous iron oxide that repels neighboring cells and matrix [29].…”
Section: Introductionmentioning
confidence: 99%
“…For larger animal studies sheep [122] and pigs [123] have been used previously, with dogs and goats also established in the field [119]. In cardiovascular applications rats are also used as a small animal model [124][125][126], with pigs generally favoured once large animal trials are required [127].…”
Section: Consideration For Selecting An Appropriate In Vivo Modelmentioning
confidence: 99%
“…However, there are some few studies which have enough similarities to justify a direct comparison. Two such studies are in Table 9 [126,129]. These studies considered CP-Mg wire in both an orthopaedics and cardiovascular location, and while the time points of analysis were not identical, they were comparable.…”
Section: Consideration For Selecting An Appropriate In Vivo Modelmentioning
confidence: 99%
“…Among the biodegradable materials, Mg is unique because of its activity in body fluids. 20 In this study, to understand how MgMPs derived from Mg corrosion interact with inflammatory cells and the implant environment, we investigated the effects of MgMps in vitro and in vivo on the inflammatory response and the ultimate effect on bone structure. Titanium particles (TiMPs) were used as a metallic material control.…”
Section: Introductionmentioning
confidence: 99%